2020
DOI: 10.5713/ajas.19.0748
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of carcass weight of Hanwoo (Korean native cattle) as a function of body measurements using statistical models and a neural network

Abstract: 30Objectives: The objective of this study was to develop a model for estimating the carcass weight of 31 Hanwoo cattle as a function of body measurements using three different modeling approaches: 1) 32 multiple regression analysis, 2) partial least square regression analysis, and 3) a neural network. 33 Methods: Data from a total of 134 Hanwoo cattle were obtained from the National Institute of Animal 34 Science (NIAS) in South Korea. Among the 372 variables in the raw data, 20 variables related to 35 carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Neural networks (NN) consist of input, hidden, and output layers, where deeper hidden layers may allow the network to better fit to the training data, at the cost of decreasing generalization ability for field or test data. For this reason, NN-based regression models mostly use two hidden-layers, such as those previously designed for draft force prediction [ 9 ], constituent properties estimation [ 21 ], and Carcass weight prediction [ 13 ]. Thus, a two-hidden layer NN architecture was adopted to estimate the AT for the agricultural tractor in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural networks (NN) consist of input, hidden, and output layers, where deeper hidden layers may allow the network to better fit to the training data, at the cost of decreasing generalization ability for field or test data. For this reason, NN-based regression models mostly use two hidden-layers, such as those previously designed for draft force prediction [ 9 ], constituent properties estimation [ 21 ], and Carcass weight prediction [ 13 ]. Thus, a two-hidden layer NN architecture was adopted to estimate the AT for the agricultural tractor in this study.…”
Section: Methodsmentioning
confidence: 99%
“…MLR-based models have been used to estimate dependent variables in various research fields, where the models are developed based on statistical analysis methods by adopting explanatory variables that are closely related to the prediction targets [ 12 ]. In general, it is important to select variables that have a great influence on the AT of a tractor, in order to develop MLR-based estimation models [ 13 ]. To date, many researchers have analyzed the major tractor parameters affecting the tractor AT.…”
Section: Introductionmentioning
confidence: 99%
“…One of the sequential model-based optimization algorithms is Bayesian Optimization [13]. Research related to hyperparameter optimization using Bayesian Optimization was carried out on the Gradient Boosted Trees algorithm by [14]. This research showed that hyperparameter optimization using Random Search for machine learning models experienced an increase in accuracy compared to not using hyperparameter optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Eyduran et al (2017) compared the predictive ability of MLR, CART, CHAID, and ANN in body weight prediction from some body measurements of the indigenous Beetal goat. Lee et al (2020) estimated the carcass weight of Hanwoo cattle as a function of body measurements of Hanwoo cattle by using MLR, PLS (Partial least squares) regression, and ANN. For the prediction of body weight in sheep breeds, Tirink (2022) evaluated the ability of BRNN (Bayesian Regularized Neural Network), SVM, RFR, and MARS algorithms.…”
Section: Introductionmentioning
confidence: 99%